Determinants of ERP Adoption in the Food and Beverage Industry: Evidence from UTAUT2 - Harsanti, Januari Pri; Warsono, Sony (Journal of Accounting Science, 2026)
General Background: Enterprise Resource Planning (ERP) systems provide solutions by integrating various business functions through automated processes. Specific Background: Empirical research on ERP adoption among Indonesian SMEs is still limited, especially regarding usage intentions and actual usage behaviour, posing practical challenges for SMEs. Knowledge Gap: This study addresses gaps in previous findings that were limited in terms of sample size, industry type, data collection techniques, and ERP components tested by MSMEs, using the UTAUT2 perspective. Objective: This study analyses the determinants of ERP usage intentions and the moderating role of ICT experience in food and beverage SMEs. Method: Primary data were collected through questionnaires distributed to owners, directors, and managers of food and beverage SMEs in five provinces in Indonesia and analysed using Partial Least Squares–Structural Equation Modelling (PLS-SEM). The final sample size was 133 respondents. Results: The results indicate that the intention to use ERP is significantly influenced by performance expectations, effort expectations, supportive conditions, habit, and information quality, while ERP usage behaviour is influenced by habit and intention to use. Novelty: This study expands on UTAUT2–ERP research by integrating information quality into the model and analysing ICT experience as a moderator for ERP usage intention and actual usage behaviour in food and beverage SMEs. Implications: These findings provide guidance for SMEs to adopt ERP and provide insights for service providers to develop more user-oriented systems and services.